REPORT ON AIRLINE SMOKING BAN RESEARCH 19880500 - 19880600 - HAMILTON FREDERICK (Tufts Archival Research Center, 2007)
Report done by Hamilton, Frederick and Schneidersd for the Tobacco Institute regarding people's reaction to the smoking bans on airplanes. Finds that the attitude of the smoker is one of resignation. Suggests that the publicizing of the two year sunset ban would help to garner support for opposing the smoking restrictions on airplanes. Includes copy of questionnaire used in study.